Beyond the random walk - Singal, Vijay (Oxford University Press, 2004)
The author distills several decades of academic research into a focused discussion of market anomalies that is both accessible and useful to people with varied backgrounds. Past empirical evidence is supplemented with author's own research using more recent data. Anomalies covered include the "December Effect," "Momentum in Industry Stocks," "S&P 500 Index Changes," "Trading by Insiders," and "Merger Arbitrage." In each chapter, the author describes the particular anomaly, explains how it occurs, shows ways to take advantage of the anomaly, and highlights the risks involved. We learn, for example, that shares of stocks that have appreciated in recent months become scarce in late December, because investors wait until January before they sell (to postpone payment of taxes on profits). This scarcity drives the price up--the "December Effect"--and smart buyers can make the equivalent of 75% annual return on a five-day investment